Is reduced graphene oxide favorable for nonprecious metal oxygen-reduction catalysts?. (June 2016) - Gao, Wei; Havas, Dana; Gupta, Shiva; Pan, Qin; He, Nanfei; Zhang, Hanguang; Wang, Hsing-Lin; Wu, Gang
Abstract: Reduced graphene oxide (rGO), as a newly emerged carbon material, has attracted great attention concerning its applications for electrocatalysts. Presently, there are mixed opinions regarding the advantages to using rGO as a support for preparing nonprecious metal catalysts for the oxygen reduction reaction (ORR). The primary goal of this work is to determine whether rGO would be favorable for non-precious metal catalysis of oxygen reduction or not. In the case of Fe-free catalysts, when polyaniline (PANI) was used as nitrogen/carbon precursor, the PANI-rGO catalyst is superior to the PANI-Ketjenblack (KJ) carbon black catalyst in terms of ORR activity and H2 O2 yield. When comparing the ORR activity of PANI-Fe-rGO to the traditional PANI-Fe-KJ, in more challenging acidic electrolyte, PANI-Fe-rGO performed no better than PANI-Fe-KJ. However, rGO does indeed enhance stability of the Fe–N–C catalyst in acidic media. In addition, in an alkaline electrolyte, ORR activity was significantly improved when using rGO in comparison to the KJ-supported Fe–N–C catalysts. Based on detailed comparisons of structures, morphologies, and reaction kinetics, the traditional KJ support with dominant microporous is able to accommodate more FeNx moieties that are crucial for the ORR in acid. Oppositely, the richness of nitrogen-doped graphene edge sites provided by rGO facilitates the ORR in the alkaline electrolyte.